(untitled) (Journal of Kidney Cancer, 2020)
Multiple combinational regimens have recently been approved and are now considered the standard of care for patients with advanced clear cell renal cell carcinoma (RCC). Several additional combinational regimens are deep in clinical assessment and are likely to soon join the crowded front-line therapeutic landscape. Most of these regimens are combinations of agents already approved as single-agents in RCC including tyrosine kinase inhibitors (TKI) and immune checkpoint inhibitors. While these new front-line regimens are associated with reliably high response rates and prolonged survival, complete and durable remissions remain limited to a small subset of patients and the vast majority of patients continue to require subsequent therapy. The need for the continued development of novel agents in RCC persists and efforts have focused on agents targeting the molecular biology of clear cell RCC and novel immunotherapies including cytokines. In this review, we discuss the progress in the development of these novel therapies in the context of the evolving standard of care for patients with advanced clear cell RCC.